A closer look at the burial rights, beliefs, and practices of the municipalities of Dulag, Leyte and Borongan, E. Samar. - Coles, Cyrill Abigail A. (Cyrill Abigail A. Coles and Dianne D. Tupaz, 2009)
This study is entitled, "A Closer Look at the Rites, Beliefs, and Burial Practices of the Municipalities of Dulag, Leyte and Borongan, Eastern Samar." This study answers the following questions: (1) What are the similarities and differences in the burial rites, beliefs, and practices followed by the people in the municipalities of Dulag, Leyte and Borongan Eastern Samar?; (2) What are the underlying reasons for such burial rites, beliefs, and practices?; (3) What are the factors that influence the beliefs and practices of the people in the municipalities of Dulag, Leyte and Borongan Eastern Samar? This study aims to explore and delineate the modes of veneration of the dead as part of the Filipino identity. It also intends to clarify the similarities and distinctions of the burial rites, beliefs, and practices of the people from the municipalities of Dulag, Leyte and Borongan, Eastern Samar. Moreover, the study employed the descriptive method of research. The respondents of the study were 10 families from the municipality of Dulag, Leyte and 10 families from the municipality of Borongan Eastern Samar, who were bereaved from Jan. 2006 to Oct. 2008. Purposive sampling was used in identifying individual research respondents. The study made use of "pagmamasid", "pakikisalamuha", "pakikilahok", at "pagtatanong" as methods of collecting information. WIth this study, it was found out that certain similarities were found out for the municipalities of Dulag, Leyte and Borongan Eastern Samar such that (1) The people from the municipalities of Dulag, Leyte and Borongan Eastern Samar follow the same sequence of burial rites from the onset of death until the fortieth day celebration. (2) They prepare the coffin, offer flowers, and say the same prayers such as the novena. (3) They conduct Pabalon or Send-off which is followed by burial procession and church ceremonials. (4) There are final ceremonies at the grave such as the opening of the coffin for last glance and offering of flowers before entombment. (5) Generally, there is linusaran or the funeral feast on the ninth day of novena and the fortieth day where prayer is offered and food is prepared. On the other hand, certain differences were also uncovered. These are (1) Although the people from both municipalities of Dulag, Leyte and Borongan Eastern Samar follow the same sequence of burial rites, they differ in burial practices and reasons behind their followed practices. (2) In the municipality of Borongan Eastern Samar, there is an association called the Kapairan where donations by the members are given to the bereaved families. And to help the family uphold the vigil, a "panagtawo" is done in the said municipality. (3) In the municipality of Dulag, Leyte, people keep a Lanterna burning throughout the vigil until the fortieth day celebration. They also celebrate Amen which includes a novena and feasting on the third day after the burial is done. Reasons for adherence to such burial rites, and practices involves adherence to everything the kalagsan (old people) especially the parapamatbat will say. These burial rites, beliefs, and practices have been a part of their tradition, handed down from generation to generation. Moreover, people from both municipalities reasoned out that they are doing it partly for the compliance and that they would lose nothing for observing such practices. Factors such as economic stability, affiliation of the dead person and its family members to different faith communities, and conviction influence the burial rites, beliefs, and practices of the people from both municipalities. Indeed, there are both similarities and differences in the burial rites, beliefs, and practices in both municipalities of Dulag, Leyte and Borongan, Eastern Samar. Also, instructions given by the kalagsan are the primary reasons for their adherences to such burial rites, beliefs, and practices. Lastly, economic stability, religion, sources of information, and conviction greatly influences such burial, rites, beliefs, and practices.